Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1158/0008-5472.can-09-2719
|View full text |Cite
|
Sign up to set email alerts
|

The Bisecting GlcNAc on N-Glycans Inhibits Growth Factor Signaling and Retards Mammary Tumor Progression

Abstract: The branching of complex N-glycans attached to growth factor receptors promotes tumor progression by prolonging growth factor signaling. The addition of the bisecting GlcNAc to complex N-glycans by Mgat3 has varying effects on cell adhesion, cell migration and hepatoma formation. Here we show that Chinese hamster ovary (CHO) cells expressing Mgat3 and the Polyoma Middle T (PyMT) antigen have reduced cell proliferation and growth factor signaling dependent on a galectin lattice. The Mgat3 gene is not expressed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 45 publications
6
75
0
Order By: Relevance
“…6). Similarly, glycosylation with the bisecting GlcNAc on N-glycans inhibits mammary tumor progression (45). Our preliminary data also revealed that a sialic acid-containing glycolipid, SSEA4, is up-regulated in the TKI-resistant mutants of lung cancer cell lines, compared with the cells with wild-type EGFR (Fig.…”
Section: Discussionsupporting
confidence: 59%
“…6). Similarly, glycosylation with the bisecting GlcNAc on N-glycans inhibits mammary tumor progression (45). Our preliminary data also revealed that a sialic acid-containing glycolipid, SSEA4, is up-regulated in the TKI-resistant mutants of lung cancer cell lines, compared with the cells with wild-type EGFR (Fig.…”
Section: Discussionsupporting
confidence: 59%
“…Sensitivity to EGF and TGFβ cytokines was rescued by hexosamine supplementation with UDP-GlcNAc or by GnT-V expression, implying that remodelling of N-glycans in tumour cells is sensitive to metabolism 161 . Accordingly, the decrease of galectin lattice interactions induced by the addition of bisecting GlcNAc N-glycans counterbalances the highly branched N-glycosylation of EGFR and PDGFR, restraining its downstream signalling and in this way retarding mammary tumour progression 166 . GnT-III overexpression reduces the ability of EGF to bind to its receptor, blocking EGFR-mediated ERK phosphorylation and increasing EGFR endocytosis 167 .…”
Section: Tumour Editingmentioning
confidence: 99%
“…The addition of this branch prevents all further branching and elongation of the glycan structures. Overexpression of GnT-III retards tumor growth and metastases 51 and antagonizes the activity of Mgat5. 52 In addition, it is thought that GnT-III is capable of regulating intracellular signaling, but these observations require further investigation.…”
Section: N-glycosylationmentioning
confidence: 99%